2018
DOI: 10.1097/aog.0000000000002372
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Risk Factors of Postpartum Stroke

Abstract: Although patients with chronic hypertension and hypertensive diseases of pregnancy are at higher risk of postpartum stroke, they account for a minority of such strokes. The majority of readmissions for postpartum stroke occur within 10 days of discharge; optimal blood pressure management may be particularly important during this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 32 publications
2
64
0
Order By: Relevance
“…Our case report concerns with a rare presentation of a postpartum ischemic stroke occurring after the cesarean section. The risk of postpartum stroke is increased during the first year after delivery according to Cheng et al, with 58.4% cases occurring within 10 days postpartum [ 3 , 5 ]. The exact mechanism for increased risk in the postpartum period is unknown, but a rise in blood pressure on three to five days due to fluid shift and impaired cerebral autoregulation can increase the chances of stroke [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our case report concerns with a rare presentation of a postpartum ischemic stroke occurring after the cesarean section. The risk of postpartum stroke is increased during the first year after delivery according to Cheng et al, with 58.4% cases occurring within 10 days postpartum [ 3 , 5 ]. The exact mechanism for increased risk in the postpartum period is unknown, but a rise in blood pressure on three to five days due to fluid shift and impaired cerebral autoregulation can increase the chances of stroke [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is approximately between 11 and 26 per 100,000 deliveries, with the risk increasing in the postpartum period [ 1 , 2 ]. According to one study, the risk of postpartum stroke readmission was highest within 10 days of hospital discharge, with 58.4% cases occurring within 10 days [ 3 ]. Timely interventions and multidisciplinary collaboration among health care professionals are imperative in diagnosing and effectively managing such cases.…”
Section: Introductionmentioning
confidence: 99%
“…1 The American College of Obstetricians and Gynecologists recommends close monitoring of patients with hypertensive disorders for the first 72 hours and again at 7e10 days after delivery, given the timing of peak blood pressures after delivery 2 and the need for optimal blood pressure management in this period of increased risk of stroke and seizure. 3 We previously showed that a text messageebased remote blood pressure monitoring program in the early postpartum period was more effective in obtaining these critical blood pressure values compared to in-person office visits in all at-risk women. 4 Non-Hispanic black women suffer a disproportionate amount of hypertensive-related morbidities and are 3 times more likely to die of preeclampsia than white women, 5 likely because of a combination of patient, community, provider, and systems factors.…”
Section: Objectivementioning
confidence: 98%
“…We used ICD-9-CM codes to identify comorbidities associated with arterial dissections and thrombosis during pregnancy: migraine, diabetes, and hypertensive disorders of pregnancy including pre-eclampsia and eclampsia. 6,[17][18][19][20] Additionally, we used previously validated ICD-9-CM codes 21 to identify ischemic stroke complicating cervical artery dissection.…”
Section: Measurementsmentioning
confidence: 99%